First report of Spirometra (Eucestoda; Diphyllobothriidae) naturally occurring in a fish host - Vettorazzi, Renzo; Norbis, Walter; Martorelli, Sergio R; Garcia, Graciela; Rios, Nestor (Folia parasitologica, 2023)
Spirometra Faust, Campbell et Kellogg, 1929 is a genus of cestodes belonging to the family Diphyllobothriidae. To date, amphibians, reptiles, and mammals are known second intermediate hosts of these parasites; humans can also be infected (the zoonotic disease is known as sparganosis or spirometrosis). Although the number of phylogenetic studies on Spirometra spp. has increased worldwide in recent years, there are few in South America. Specifically in Uruguay, molecular studies have shown that tapeworms of S. decipiens (Diesing, 1850) complexes 1 and 2 are present in this country. In this study, we characterised the larvae of Spirometra present in the annual fish Austrolebias charrua Costa et Cheffe. Phylogenetic analysis of the cytochrome c oxidase subunit I (COI) sequences of these larvae showed that they belong to S. decipiens complex 1. This is the first report of teleost fishes serving as a second intermediate host for tapeworms of the genus Spirometra in nature.
Keywords: savci; Humans; Cestode Infections; Phylogeny; ryby; Spirometra; lidé; Parasites; zvířata; Mammals; Spirometra decipiens; Fishes; Austrolebias; fylogeneze; cestodózy; Uruguay; South America; Animals; molecular characterisation; Cestoda